2010
DOI: 10.1083/jcb.201003014
|View full text |Cite
|
Sign up to set email alerts
|

VASP is a processive actin polymerase that requires monomeric actin for barbed end association

Abstract: Visualization of VASP tetramers interacting with static and growing actin filaments in vitro by TIRF microscopy leads to a new model for VASP-mediated actin filament assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
330
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(369 citation statements)
references
References 59 publications
24
330
3
Order By: Relevance
“…In the case of the Arp2/3 complex, CP promotes the quantity and quality of the branched actin arrays created by Arp2/3, such as lamellipodia and pseudopodia, by accelerating Arp2/3 complex-dependent nucleation and by promoting optimal branching within the resulting network (4,5). Formins and VASP, conversely, consider CP a "pest" and use physical mechanisms to keep it at bay as they build linear actin structures such as filopodia (48,49). Importantly, although formins are fairly effective at physically shielding the barbed end from CP, it is likely that their robustness as filopodia generators in vivo would be increased by a reduction in CP levels (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the Arp2/3 complex, CP promotes the quantity and quality of the branched actin arrays created by Arp2/3, such as lamellipodia and pseudopodia, by accelerating Arp2/3 complex-dependent nucleation and by promoting optimal branching within the resulting network (4,5). Formins and VASP, conversely, consider CP a "pest" and use physical mechanisms to keep it at bay as they build linear actin structures such as filopodia (48,49). Importantly, although formins are fairly effective at physically shielding the barbed end from CP, it is likely that their robustness as filopodia generators in vivo would be increased by a reduction in CP levels (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…The single-molecule fluorescence colocalization techniques used here are powerful tools for directly observing binding and deciphering complex reaction mechanisms (32)(33)(34)(35)(36). These techniques allowed us to directly measure key features of Arp2/3 complexmediated branch formation, including Arp2/3 binding and dissociation rates, branch formation efficiency, and activation time, and to determine how these parameters are affected by VCA.…”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to formins, they deliver actin monomers directly to filament barbed ends by virtue of their GAB domains (6,9,19,20). Moreover, PFN appears dispensable for VASP-mediated filament elongation in vitro (6,20), albeit some studies have reported increased filament elongation rates in the presence of PFN (19,21). Finally, because single Ena/VASP tetramers are not as processive as formins, they consequently only poorly protect barbed end growth from capping protein (CP) in solution (6,19,20).…”
mentioning
confidence: 99%
“…Comparable to formins, Ena/VASP proteins associate with growing barbed ends and accelerate filament elongation twofold to sevenfold (6,9,19,20). However, contrary to formins, they deliver actin monomers directly to filament barbed ends by virtue of their GAB domains (6,9,19,20).…”
mentioning
confidence: 99%